Three new species of Gelechiidae (Lepidoptera) from Panama - Chang, Patricia Esther Corro; Bidzilya, Oleksiy (Zootaxa, 2020)
Aristotelia barriosi sp. nov. (Veraguas Province, Santa Fe NP), Agnippe tarakanovi sp. nov. (Herrera Province, Sarigua NP) and Chionodes sariguaensis sp. nov. (Herrera Province, Sarigua NP) are described from Panama. Adults and the genitalia of both sexes for all species and the habitats of two latter species are illustrated.